A nickel-salphen type complex with a heteropicene backbone - Elbert, Sven; Rominger, Frank; Mastalerz, Michael (Zeitschrift für anorganische und allgemeine Chemie, 2018)
Acenes and heteroacenes as well as other larger fused aromatics and heteroaromatics are per se interesting for organic electronics. Among the large variety of such compounds those annulated π systems that bear multidentate complexation sites for transition metals are rare. This is even more true, the larger the π systems are. Picene is an alternating angular annulated π system consisting of five benzene rings. Here, the synthesis of a heteropicene that contains both thiophene and pyridine rings is introduced, whereas the nitrogen atoms are arranged in a phenanthroline subunit to which phenol units are connected, forming a tetradentate ligand. The complexation of NiII by this ligand is described and analysed by single-crystal X-ray diffraction as well as UV/Vis spectroscopy.